Aerobic Iron(III)-Catalyzed Direct Thiolation of Imidazo[1,2-a]pyridine with Thiols - Qin, Ling; Wu, Hui-bin; Weng, Lidong; Shen, Qun; Chen, Huoji (SynOpen, 2020)
A novel and efficient iron(III)-catalyzed regioselective C-3 sulfenylation of imidazo[1,2-a]pyridines with thiols under oxygen atmosphere has been developed. The reaction proceeds in moderate to good yields with a broad range of substrates, providing a novel, efficient and green route for accessing synthetically useful C3-sulfenated imidazo-[1,2-a]pyridines. Moreover, the fluoride-containing C3-sulfenated imidazo-[1,2-a]pyridine 3ai exhibited superior anticancer activity and good safety profiles.
Keywords: iron-catalyzed; thiolation; imidazo[1,2-a]pyridine; thiols; anticancer activity